HIV and AIDS knowledge, attitudes, behaviour and practices of student teachers in Namibia - Mamvura-Gava, Victoria Siphiwe (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil) -- Stellenbosch University, 2008.